CITED2 inhibits STAT1‐IRF1 signaling and atherogenesis. Issue 9 (7th August 2021) - Zafar, Atif; Pong Ng, Hang; Diamond‐Zaluski, Rachel; Kim, Gun‐Dong; Ricky Chan, Ernest; Dunwoodie, Sally L.; Smith, Jonathan D.; Mahabeleshwar, Ganapati H.
Abstract: Macrophages are the principal component of the innate immune system. They play very crucial and multifaceted roles in the pathogenesis of inflammatory vascular diseases. There is an increasing recognition that transcriptionally dynamic macrophages are the key players in the pathogenesis of inflammatory vascular diseases. In this context, the accumulation and aberrant activation of macrophages in the subendothelial layers govern atherosclerotic plaque development. Macrophage‐mediated inflammation is an explicitly robust biological response that involves broad alterations in inflammatory gene expression. Thus, cell‐intrinsic negative regulatory mechanisms must exist which can restrain inflammatory response in a spatiotemporal manner. In this study, we identified CBP/p300‐interacting transactivator with glutamic acid/aspartic acid‐rich carboxyl‐terminal domain 2 (CITED2) as one such cell‐intrinsic negative regulator of inflammation. Our in vivo studies show that myeloid‐CITED2‐deficient mice on the Apoe −/− background have larger atherosclerotic lesions on both control and high‐fat/high‐cholesterol diets. Our integrated transcriptomics and gene set enrichment analyses studies show that CITED2 deficiency elevates STAT1 and interferon regulatory factor 1 (IRF1) regulated pro‐inflammatory gene expression in macrophages. At the molecular level, our studies identify that CITED2 deficiency elevates IFNγ‐induced STAT1 transcriptional activity and STAT1 enrichment on IRF1 promoter in macrophages. More importantly, siRNA‐mediated knockdown of IRF1 completely reversed elevated pro‐inflammatory target gene expression in CITED2‐deficient macrophages. Collectively, our study findings demonstrate that CITED2 restrains the STAT1‐IRF1 signaling axis in macrophages and limits the development of atherosclerotic plaques.